Skunks - McGill, Jordan (2018)
Skunks use scent to defend themselves. Skunks use their long, sharp claws for digging in the dirt and searching for food. Discover more facts about these interesting animals in Skunks. Each World Languages title includes access to ten eBooks in ten languages! Our language toggle bar allows you to easily switch between English, Arabic, French, German, Hindi, Korean, Mandarin, Russian, Spanish, and Tagalog with a simple click. The full audio feature allows readers to listen to the text in their own language as they flip through the book. World Languages works on all platforms, including standard desktops, tablets, and SMART Boards.
Ages 4-8